Effect of dietary oregano oil on growth performance, disease resistance, intestinal morphology, immunity, and microbiota of hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) - Xin, Yu; Liu, Hao; Yan, Xiaobo; Huang, Weibin; Pan, Simiao; Zhou, Menglong; Lu, Baiquan; Tan, Beiping; Dong, Xiaohui; Yang, Yuanzhi (Frontiers in Marine Science, 2022)
The study aimed to investigate the effects of oregano oil (OO) supplement in diet on the growth performance, disease resistance, immunity and intestinal health of hybrid grouper. Six isonitrogenous and isolipid diets were fed to the grouper with an initial weight of 19.10 ± 0.12 g for 8 weeks, which dietary OO level were 0 (control), 0.1 (OO-0.1), 0.3 (OO-0.3), 0.6 (OO-0.6), 0.9 (OO-0.9), 1.2 (OO-1.2) g kg-1 respectively. The results showed that there were no significant differences of growth performance among the 6 groups, while OO supplement could improve disease resistance ability of grouper. Our findings have demonstrated that oregano oil supplement, especially 0.3 g kg-1 could improve intestinal morphology via increasing villus number and muscle thickness, elevate digestive enzyme activities such as AMS and lipase. 0.3 g kg-1 OO supplement also can activate antioxidant defense system, reduce Nrf2/Keap1 expression and then enhance the immune ability via ACP, LYS, C3 and tight junction-associated signaling pathways in hybrid grouper. Meanwhile, the relative abundance of Firmicutes and Bacteroidetes in OO-0.3 group was significantly higher than that of control group (P < 0.05), while the relative abundance of Proteobacteria showed a basically opposite trend (P < 0.05). These findings suggested that dietary OO supplementation could significantly improve intestinal health, induce antioxidant defense system and immunity, which means OO could be used as a functional feed additive to protect the intestine. And the appropriate addition level of OO should be 0.3 g kg-1 .